Rights of Armed Conflict Victims in Nepal (Sambahak: Human Rights Journal, 2024)
The conflict affected victims are those people who are subject to enforced disappearance, killings of the people in the civil war, women from lower caste are exposed to sexual violence, children are subject to recruitment by the Maoist, torture survivors and the people displaced from the conflict affected area in the ten-year armed conflict in Nepal. The family of the conflict affected victims have right to know the status of their loved ones either they are alive or dead as per the Constitution of Nepal. The Government have ratified the several International Human Rights Conventions. This article aims to critically analyze the implementation status of the International Human Rights Instrument, Geneva Conventions, national legislations about the rights of armed conflict victims as well as the landmark judgment preceded by the Supreme Court of Nepal for advocating the guarantee of the justice to the armed conflict victims. Nepal is state party of the Geneva Conventions, 1949 but it has not ratified the Protocols of the Geneva Conventions, 1977. Nepal has not ratified the Convention on Protection of All Persons Against the Enforced Disappearance, 2006. The national legislations have addressed the rights of the victim of the armed conflict, but they are not implemented properly by the regulatory authorities such as Enforced Disappearance Enquiry, Truth and Reconciliation Commission, Attorney General and National Human Rights Commission etc. Despite of their institutionalization the voices of conflict affected victims of Nepal are not heard and they are not benefitted by the justice system.